2019
DOI: 10.1002/malq.201800056
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐embeddability spectra and bases of spectra

Abstract: We study degree spectra of structures with respect to the bi‐embeddability relation. The bi‐embeddability spectrum of a structure is the family of Turing degrees of its bi‐embeddable copies. To facilitate our study we introduce the notions of bi‐embeddable triviality and basis of a spectrum. Using bi‐embeddable triviality we show that several known families of degrees are bi‐embeddability spectra of structures. We then characterize the bi‐embeddability spectra of linear orderings and study bases of bi‐embeddab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Informally speaking, the poset CR(L ) contains all computable copies of L , up to computable bi-embeddability. This observation provides a connection to the recent study of bi-embeddability spectra [14] and computable bi-embeddable categoricity [15,16].…”
Section: Pr(s ) = ({Deg Pr (A )supporting
confidence: 63%
“…Informally speaking, the poset CR(L ) contains all computable copies of L , up to computable bi-embeddability. This observation provides a connection to the recent study of bi-embeddability spectra [14] and computable bi-embeddable categoricity [15,16].…”
Section: Pr(s ) = ({Deg Pr (A )supporting
confidence: 63%
“…Knight [16] showed that isomorphism spectra of automorphically trivial structures contain only one Turing degree and that the isomorphism spectra of automorphically nontrivial structures are upwards closed in the Turing degrees. In [7] the authors showed that if A is automorphically trivial and B ≈ A, then B ∼ = A. Thus, as every biembeddability and elementary bi-embeddability spectrum is a union of isomorphism spectra, Knight's result carries over to this setting.…”
Section: Definition 44 a Category C Is Degree Invariant If For Every ...mentioning
confidence: 99%
“…Recently, researchers initiated the study of degree spectra with respect to other model theoretic equivalence relations such as bi-embeddability [7], elementary bi-embeddability [20], elementary equivalence [1–3], or equivalence [8]. One of the main goals in this line of research is to distinguish these equivalence relations with respect to the degree spectra they realize.…”
Section: Introductionmentioning
confidence: 99%
“…Degree spectra with respect to another natural equivalence relation, that of bi-embeddability, are considered in [4].…”
Section: Introductionmentioning
confidence: 99%